Do proposto ao vivido : estudo sobre a política de assistência estudantil no Campus Vacaria do IFRS - Costa, Adriana Maria da Silva (2025)
The expansion of access policies to Federal Institutes of Education, Science, and Technology has generated ongoing concern regarding student permanence in these promising educational institutions. In this context, through a strong correlation of forces between the State and society, the National Student Assistance Policy was established, primarily to assist students in situations of social vulnerability, providing the necessary resources for access, permanence, and successful completion of their studies. Understanding policy as a right and then examining how it is implemented in practice constitutes the main scope of this research. The policy implementation phase encompasses decisions made in practice. The research is organized into four dimensions: (1) the normative structure of the policy; (2) institutional/organizational dynamics; (3) stakeholders' conceptions of the policy; and (4) implementation processes. To this end, the theoretical framework is the policy cycle of Stephen Ball (1994, 1998, 2011) and his colleagues, as well as the studies of Jefferson Mainardes (2006, 2010, 2011, 2016). The objective of this research was to understand and analyze the process of recontextualizing and implementing the Student Assistance policy at the IFRS Vacaria Campus in light of the Policy Cycle and the translation and performance theories of S. Ball and his colleagues. The research was both qualitative and quantitative in nature. The IFRS Vacaria RS Campus served as the locus of study. The field research was conducted in 2025 through interviews with four staff members and a questionnaire administered to 62 student users of the policy. The results reinforce the relevance of normative structures and organizational contexts for the implementation and understanding of the Student Assistance Policy at the IFRS Vacaria Campus, Rio Grande do Sul. They also highlight the relevance of its applicability to students, particularly regarding the payment of the maintenance allowance. It is worth noting, however, that the policy analyzed at the Vacaria Campus, Rio Grande do Sul, presents obstacles in its normative structure and institutional/organizational conditions regarding the context of practice, so that, in some respects, these have negatively impacted its implementation. These obstacles are consistent with the findings of Stephen Ball and colleagues, who emphasize the importance of utilizing the stages of the policy cycle when proposing to study educational policy studies. Ultimately, despite the various implementation challenges identified, such as a lack of a minimum staff, a mismatch in the dissemination and clarification process, and insufficient resources, the stakeholders perceived the policy as crucial for the inclusion of students in situations of social and economic vulnerability in Integrated Technical Courses in Secondary Education.